BL Lacertae: a study of quasi-stationary feature trajectories in the inner part of a relativistic jet - Hambardzumyan, L. A.; Arshakian, T. G.; Pushkarev, A. B.
Radio interferometric VLBA observations allow the mapping of relativistic jets with sub-milliarcsecond resolution, which enables the studying of the fine structure and dynamics of the jets in active galactic nuclei. A quasi-stationary component (QSC) near the radio core is observed in a number of blazars. VLBA monitoring of the BL Lacertae object at 15 GHz has shown that the QSC located at about 0.26 mas from the radio core is followed by superluminal components, whose dynamics forms the structure of the jet on parsec scales. We study the trajectory of the QSC using the 164 epochs taken from the MOJAVE (Monitoring Of Jets in Active galactic nuclei with VLBA Experiments) database. The trajectory of the QSC is complex, and we use a moving average smoothing filter to track the intrinsic motion of the QSC. At small time scales of few months, we find that the QSC makes a swinging motion with about 23 reversals over 20 years with an average period of about 0.5 years. The trajectories between the reversals have varying lengths with a mean value of about 30 μas (∼ 0.04 pc) and curvatures of varying degrees. Number of clockwise reversals are about twice less than that of anticlockwise reversals.
Keywords: Astronomy